Modular design towards the circular economy – From ‘making to unmake’ to ‘making to remake' - Lucia Pietroni; Alessandro Di Stefano; Daniele Galloppo (Agathón)
Given the recent debate regarding the transition to the Circular Economy, Design for Modularity strategies play a decisive role in the process of transforming the current economic model from linear to circular. By describing some recently developed modular product case studies, this article intends to outline the considerations developed in the field of design culture for sustainability, on the concept of modularity. In recent years, this has shifted from the industrial logic of ‘making to unmake’, namely designing modular and disassemblable products mainly to recycle their end-of-life materials, to the logic of ‘making to remake’, to increase their circularity and durability, thereby making them reusable, repairable and remanufacturable. The objective of this contribution is to re-examine the concept of ‘modularity’ in the Circular Economy scenario, as a strategic design lever to extend the useful life of industrial products.